Critical Positive Youth Development in Non-Traditional Sport Spaces - Kalyn McDonough Smith; Kelly M. Clanchy; Tarkington J Newman; Michael A. Hemphill (Youth)
Youth sport has been recognized as a unique learning context for positive youth development (PYD); yet, as society’s critical consciousness continues to progress, limitations of PYD have been acknowledged. Thus, youth sport scholars have begun to embrace critical perspectives to interrogate the systems and institutions of sport and society that influence the healthy development of all youth. This has included researchers and practitioners alike, adopting critical PYD (CPYD) as a means to empower young people to question and challenge their histo-contemporary experiences and support collective action towards social change. Our article explores the concept of CPYD and social justice life skills within ‘non-traditional’ sport spaces, including practice examples from the fields of youth disability sport and sport in youth justice. The first practice example provides an in-depth discussion of the theoretical principles of CPYD and their applicability within youth disability sport. The second practice example outlines the practical use of social justice life skills in sport programs within the youth justice system. Together, the practice examples from the field highlight both the theoretical and practical applications of CPYD and social justice life skills within real-world settings, and valuable implications are identified for research and practice moving forward.